O desafio do Lar em fluxos migratórios laborais - Moura, Monique Limaverde (2015)
This document consists of a graduation paper of the Course of Architecture and Urbanism at the Federal University of Ceará, through the study of migration flows generated by the Industrial and Port Complex of Pecém and results in an architectural project of a residence for an employee of CIPP and your family.